Quasi-global soil moisture and freeze-thaw retrieval using Fengyun-3G GNSS-R observations - Wentao Yang; Fei Guo; Xiaohong Zhang; Zhiyu Zhang; Yifan Zhu; Zheng Li; Ziheng Wu; Dengkui Mei (Geo-spatial Information Science)
Fengyun-3G (FY-3G) is one of the satellites in the Fengyun series, equipped with a Global Navigation Satellite System-Reflectometry (GNSS-R) payload. FY-3G has been operating successfully for several months and has accumulated sufficient observations. To explore the land remote sensing potential of FY-3G GNSS-R observations, this study conducted surface soil moisture (SM) and freeze-thaw (F/T) state retrievals using FY-3G GNSS-R observations. The results show that the overall root mean square error (RMSE) and correlation (R) of the FY-3G SM retrievals compared to the contemporaneous Soil Moisture Active Passive (SMAP) SM are 0.056 [Formula: see text]/[Formula: see text] and 0.91, respectively. The accuracy of the FY-3G F/T retrievals is 84.3%. In addition, independent stations similarly demonstrated the good performance of FY-3G observations for SM and F/T retrievals and showed that FY-3G and SMAP have comparable monitoring capabilities. This study successfully demonstrates the capability of FY-3G in SM and F/T monitoring. This will enlarge the range of the application of the Fengyun satellite for monitoring land parameters in the future.